The role of game in social interaction - Chuloshnikova, Maryna (Actual Problems of Mind, 2017)
The paper analyzes the game in social interaction and manifestation of the game in public relations. The author concludes that game must remain out of real social interaction. Uncontrollable introduction of game in public relations leads to negative consequences.